Woman and Pleasure. The Attitude of Polish Female Students to Pleasure, Based on Empirical Studies from 2020 - Katarzyna Uklańska (The Francis de Sales Scientific Society (TNFS.PL), 2021)
Pleasure is an important component of the contemporary culture of consumption. The pursuit of it is encouraged by, inter alia, media, shopping malls, but also other types of institutions. This incentive is conveyed through, inter alia, advertising. Symptoms of this culture can also be observed at universities. Today's students are only familiar with this reality and have no experience of the "culture of scarcity". Therefore, it is worth asking if young women desire pleasure, whether it is important to them, and what is its place among other aspirations. The aim of the article is to analyze the hierarchy of values of young women and the position of pleasure in it. This will be achieved through referring to their choices of important values in life - those which constitute the meaning of their lives, and the priority of moral values or pleasure as essential criteria for selection. Among the surveyed women, "the hedonists" will also be indicated - namely women who indicated pleasure as their supreme value - and their axiological choices will be analyzed. The analysis is based on the results of the study "Academic youth on family and religion 2020" conducted among academic youth in 2020 by the Research Laboratory of the Polish Measurement of Attitudes and Values (PPPiW), in which the author of the article also participated.